(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
I’m not writing of all those innocent young girls I’vewritten of till now; girls who ultimately mated themselves with the rightmen. Nor am I writing a story of acallous, insensitive husband and a sensitive, suffering wife. I’m writing of us. Of Mohan and me. And I know this – you can never be theheroine of your own story. Self-revelation is a cruel process. The realpicture, the real ‘you’ never emerges. Looking for it is as bewildering as trying to know how you reallylook. Ten different mirrors show you tendifferent faces.1 (TLS-1)